2019
DOI: 10.3892/br.2019.1256
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key miRNAs in papillary thyroid carcinoma based on data mining and bioinformatics methods

Abstract: MicroRNAs (miRNAs) are a class of short (approximately 22 nucleotides), non-coding and endogenous RNA molecules that play pivotal roles in the occurrence and development of cancer. The present study aimed to investigate key miRNAs involved in papillary thyroid carcinoma (PTC). Two independent datasets (GSE73182 and GSE113629) were obtained from the GEO database. The differentially expressed miRNAs (DEmiRNAs) between PTC tissues and normal thyroid tissues were analyzed by GEO2R with the Limma R package. Key miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 8 Emerging evidence shows that the progression and metastasis of PTC and other human cancers are mediated by dysregulation of miRNAs. 9 Here we noted that miR-181a has been extensively studied in a wide variety of human cancers, including breast, 10 cervical, 11 and gastric cancers. 12 A recent study has shown that miR-181a promotes cell proliferation and inhibits apoptosis in thyroid cancer, 13 and other research shows upregulation of miR-181a content in PTC cell-derived EXs.…”
Section: Introductionmentioning
confidence: 97%
“… 8 Emerging evidence shows that the progression and metastasis of PTC and other human cancers are mediated by dysregulation of miRNAs. 9 Here we noted that miR-181a has been extensively studied in a wide variety of human cancers, including breast, 10 cervical, 11 and gastric cancers. 12 A recent study has shown that miR-181a promotes cell proliferation and inhibits apoptosis in thyroid cancer, 13 and other research shows upregulation of miR-181a content in PTC cell-derived EXs.…”
Section: Introductionmentioning
confidence: 97%
“…Research also found that miR-3613-5p was a key miRNA in cell malignancy of liver cancer induced by a atoxin B1 [39]. Wang X et al [40] found that miR-221-3p was independent of the prognosis of hepatocellular carcinoma (HCC), while Wang J et al [41] reported the key role of miR-221-3p in thyroid cancer. Moreover, Fang R et al [42] established a prognostic model for breast cancer based on 13 miRNAs including miR-221-3p.…”
Section: Discussionmentioning
confidence: 99%
“…Research also found that miR-3613-5p was a key miRNA in cell malignancy of liver cancer induced by aflatoxin B1 37 . Wang et al 38 found that miR-221-3p was independent of the prognosis of hepatocellular carcinoma (HCC), while Wang et al 39 reported the key role of miR-221-3p in thyroid cancer. Moreover, Fang et al 40 established a prognostic model for breast cancer based on 13 miRNAs including miR-221-3p.…”
Section: Discussionmentioning
confidence: 99%